Determination of Stress Shear on Interface of Reinforced Concrete Jacketed Beam - HWAIJA, Bassam; NADDAF, Qusai; SBHI, Mirna (Latakia University Journal -Engineering Sciences Series, 2020)
Strengthening and retrofitting of existing beams have been widely discussed topics for the last decade. A great number of existing beams need rehabilitation or strengthening because of improper design or construction, change of the design loads, damage caused by environmental or human factors, seismic events, etc. A popular technique for increasing the capacity of reinforced concrete beams involves the casting of a new layer, reinforced or not, on the tensile or the compressive side of the beam. Shear stress is introduced at the interface between the old and the new concrete, and it affects the behavior of the composite element. In this paper, an analytical procedure is conducted on reinforced concrete jacketed beams using ANSYS software, to determination the effect of vertical shear stress, percentage of reinforcement that cross the interface and the growth of cracks on the interfacial shear stress. This study presents that the interfacial shear stress equal to vertical shear stress at the same section at the supports. In the middle of span, the interfacial shear stress decreases after 25% of the applied load and then absents. The interfacial shear stress increases with increasing the percentage of reinforcement that cross the interface. This stress decreases with the growth of cracks until absents when cracks up to interface. إن عمليات التقوية والتدعيم للجوائز القائمة من أكثر المواضيع التي تمت مناقشتها بشكل واسع في العقد الأخير, حيث يوجد الكثير من الجوائز بحاجة إلى التقوية أو إعادة التأهيل بسبب التصميم أو التنفيذ الخاطئ, أو بسبب تغير الحمولات التصميمية أو أي ضرر يمكن أن ينتج من العوامل البيئية أو البشرية أو بسبب الأفعال الزلزالية وغيرها. من أكثر الطرق استخداماً لزيادة قدرة تحمل الجوائز البيتونية المسلحة هي بإضافة طبقة بيتونية سواء كانت مسلحة أو غير مسلحة في الجانب المشدود أو المضغوط للجائز البيتوني. تنتج إجهادات قاصة عند السطح البيني بين البيتون القديم والبيتون الجديد تؤثر على سلوك المقطع المركب. تم في هذا البحث إجراء دراسة تحليلية باستخدام برنامج ANSYS على جوائز بيتونية مسلحة مدعمة بقمصان بيتونية لتحديد تأثير كل من الإجهادات القاصة الشاقولية ونسبة التسليح العرضي الذي يعبر السطح البيني وتطور التشققات على الإجهادات القاصة البينية. أظهرت هذه الدراسة أن الإجهادات القاصة البينية تساوي الإجهادات القاصة الشاقولية عند نفس المقطع وذلك عند المساند, أما في وسط المجاز تنخفض الإجهادات القاصة البينية بعد الوصول ل 25% من الحمولة المطبقة حتى تنعدم. بزيادة نسبة التسليح الذي يجتاز السطح البيني تزداد الإجهادات القاصة البينية, ومع تطور التشققات تقل الإجهادات القاصة البينية حتى تنعدم عندما تصل التشققات للسطح البيني.